Characterization of the nurses and the care practice in neonatal intensive care unit - Coutinho, Rosalete Landim de Castro; Rolim, Karla Maria Carneiro (Rev Rene, 2005)
This is a quantitative, exploratory and descriptive study in which the aim is to characterize the profile of nurses who work in Neonatal Intensive Care Units of teaching maternity hospitals in Fortaleza-CE. The data was collected through a questionnaire answered by 43 nurses. The results showed that most of these professionals are married women with children, within the age range of 22 to 56 years old, most of them public university graduates with post graduation degrees in different areas and professional practice in this field varying from 1 to 20 years. The findings also revealed that none of the professionals, until data collection, had a post graduation degree in newborn care and that most of them are subject to inadequate workloads in order to earn more money and obtain better salaries.